Efficacy of differents treatments in guinea figs (Cavia porcellus) infected with Chirodiscoides caviae - Alexandre, Sandra Regina; Bressan, Maria Cecilia Reale Vieira (Brazilian Journal of Veterinary Research and Animal Science, 1994)
In order to improve the sanitary control of a guinea pig colony, a study was conducted to determine the presence and identification of ectoparasites as well the efficacy of ectoparasiticides most commonly used in mites control. The guinea pigs mite Chirodiscoides caviae was identified with a high level of infestation, 314 mites per cm2 of hair. The infested guinea pigs were submitted to different treatment with Cypermethrin high-cis (0.1%), Trichlorfon (0.1%), Malathion (0.2%) and Monossulfiran (12.5%). All there products showed efficacy.